Wykorzystanie głównych składowych w analizie regresji wielorakiej - Sztemberg-Lewandowska, Mirosława (Principal Components in Regression Analysis, 2006)
In multiple regression, one of the major difficulties is the problem of multicollinearity. To overcome this problem various approaches have been proposed. One possibility is to use principal components.The article presents the usage of principal components in regression analysis to reduce the collective features of chocolate in order to obtain a few components, which contribute mostly to the popularity of the product on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 50-57